Fluidity amidst structure: multi-racial identity constructions across the life course of Malaysians and Singaporeans. (4th May 2019) - Reddy, Geetha
ABSTRACT: Multi-racial identity construction is understood to be fluid, contextual and dynamic. Yet the dynamics of multi-racial identity construction when racial identities are ascribed and formulated as static by governments is less explored in psychological studies of race. This paper examines the dynamics of racial identity construction among multi-racial Malaysians and Singaporeans in a qualitative study of 31 semi-structured interviews. Thematic analysis was used to identify the different private racial identity constructions of participants who were officially ascribed with single racial identities at birth. Participants reflected on the overwhelming influence of the state and significant Others in limiting their ability to express their multiple racial identities when they were in school, and highlighted their capacity to be agentic in their private racial identity constructions when they were older. This paper shows that across the life course multi-racial individuals possess (1) the ability to adopt different racial identity positions at different times, (2) the ability to hold multiple racial identity constructions at the same time when encounters with Others are dialogical, (3) the reflexivity of past identity positions in the present construction of identities.